A developmental atlas of male terminalia across twelve species of Drosophila - Urum, Anna; Rice, Gavin; Glassford, William; Yanku, Yifat; Shklyar, Boris; Rebeiz, Mark; Preger-Ben Noon, Ella (Frontiers in Cell and Developmental Biology, 2024)
How complex morphologies evolve is one of the central questions in evolutionary biology.Observing the morphogenetic events that occur during development provides a unique perspective on the origins and diversification of morphological novelty. One can trace the tissue of origin, emergence, and even regression of structures to resolve murky homology relationships between species. Here, we trace the developmental events that shape some of the most diverse organs in the animal kingdom -the male terminalia (genitalia and analia) of Drosophilids. Male genitalia are known for their rapid evolution with closely related species of the Drosophila genus demonstrating vast variation in their reproductive morphology. We used confocal microscopy to monitor terminalia